1992
DOI: 10.1136/pgmj.68.804.811
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of one versus three doses of Augmentin as wound prophylaxis in at-risk abdominal surgery

Abstract: Summary:In a randomized prospective trial of prophylactic antibiotics in at-risk abdominal surgery, one dose ofintravenous Augmentin (amoxycillin 250 mg and clavulanic acid 125 mg) on induction has been compared with three 8 hourly doses in 900 patients. Wound infection rates which included minor and delayed infections were very similar in those given one dose: 48/449 (10.7%) compared with those given three doses: 49/451 (10.9%) 95% confidence limits -4.25% + 3.9%.There were more septic and sepsis-related deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…No differences in efficacy between first-and secondgeneration cephalosporins were found. Amoxicillin-clavulanate 279,282,283,299 and ciprofloxacin 269,300 were also evaluated with similar results. Relatively few studies have compared the efficacy of different agents in reducing postoperative infection rates.…”
Section: Gastroduodenal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences in efficacy between first-and secondgeneration cephalosporins were found. Amoxicillin-clavulanate 279,282,283,299 and ciprofloxacin 269,300 were also evaluated with similar results. Relatively few studies have compared the efficacy of different agents in reducing postoperative infection rates.…”
Section: Gastroduodenal Proceduresmentioning
confidence: 99%
“…256,[279][280][281][282][283][284]288,290,297 The available data indicate that single-dose and multiple-dose regimens are similarly effective. Three studies compared single-and multiple-dose regimens of cefamandole, 294 amoxicillin-cluvulanate, 299 and ampicillin-sulbactam and cefazolin. 253 There were no significant differences in SSI rates.…”
Section: Gastroduodenal Proceduresmentioning
confidence: 99%
“…No differences in efficacy between first-and second-generation cephalosporins were SURGICAL PROPHYLAXIS GUIDELINES found. Amoxicillin-clavulanate [279,282,283,299] and ciprofloxacin [269,300] were also evaluated with similar results. Relatively few studies have compared the efficacy of different agents in reducing postoperative infection rates.…”
Section: Efficacymentioning
confidence: 99%
“…Seven trials did not find differences in the SWI rate between co-amoxiclav arms and other antibiotics such as cephradine plus metronidazole, 145 gentamicin plus metronidazole, 61 mezlocillin alone or plus metronidazole, 87,100 and cefotetan. 19 Bates and co-workers 23 compared a single dose of co-amoxiclav with three doses of co-amoxiclav. The difference in the rate of SWI was not statistically significant (odds ratio = 1.41; 95% CI: 0.71, 2.82).…”
Section: Co-amoxiclavmentioning
confidence: 99%
“…None of these trials found a significant difference in postoperative SWI between single-dose and multiple-dose regimens. The antibiotics that were investigated in these trials were cefoxitin, 38,81 cefuroxime plus metronidazole, 14 metronidazole, 34 ampicillin plus metronidazole, 69,74 co-amoxiclav, 23 latamoxef, 60 mezlocillin plus metronidazole, 27,58,98 ticarcillin/clavulanic acid, 40 cefotaxime plus metronidazole, 81 gentamicin plus ornidazole, 154 piperacillin plus tinidazole, 148 doxycycline, 54 and cefotaxime. 88 When the results from these 17 trials were pooled, there was no significant difference between the single-and multiple-dose groups (10.6% versus 9.7%; odds ratio = 1.17; 95% CI: 0.89, 1.54).…”
Section: Single-dose Versus Multiple-dose Regimensmentioning
confidence: 99%